The Quality Analysis of Fresh Mackarel Tuna under Different Icing Durations in Cold Storage Based on pH and Organoleptic Values - Vebiola Pesondolang; Febrina Olivia Akerina; Yubelina Hibata; Femsy Kour (BIOSAINSTEK, 2026)
Mackerel tuna (Euthynnus affinis) is one of the most widely consumed marine fish species in Tobelo, North Halmahera, Indonesia. Due to its highly perishable nature, maintaining freshness during postharvest handling is essential to preserve product quality and ensure consumer safety. This study aimed to evaluate the freshness of mackerel tuna during chilled storage using ice by assessing the changes in pH and organoleptic characteristics. The experiment was conducted from May to June 2025. Fresh fish were stored on ice and evaluated at 0, 4, 8, and 12 h after arrival at the laboratory. The pH was measured in triplicate, and the organoleptic quality was assessed by 30 untrained panelists based on the Indonesian National Standard (SNI) for fresh fish. The data were descriptively analyzed and presented in tables and figures. The results demonstrated that the pH of mackerel tuna decreased from 0 to 8 hours of storage, corresponding to the rigor mortis phase, and subsequently increased at 12 hours, indicating the onset of post-rigor biochemical changes. Organoleptic scores gradually declined during storage but remained within the acceptable range for fresh fish samples. The mean scores were 7.67–8.93 for eye appearance, 8.00–9.00 for gill appearance, 7.87–9.00 for surface slime, 7.80–8.80 for flesh appearance, 7.93–8.87 for odor, and 8.07–9.00 for texture appearance. All organoleptic values remained above the minimum acceptance score of 7.0 specified by the Indonesian National Standard (SNI), indicating that the fish maintained acceptable freshness throughout the 12-h storage period under iced conditions.